DIRECTION OF STUDENTS TO NATIONAL CRAFT PROFESSIONS IN SCHOOL TECHNOLOGY EDUCATION (American Journal of Interdisciplinary Research and Development, 2023)
The article describes in detail the essence of directing students to national craft professions in school technology education.